Organizing in the face of risk and threat - Czarniawska-Joerges, Barbara (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2009)
There are no prescriptions for organizing in the face of risk and threat, but the accumulating experience shows that a well-rehearsed improvisation brings much better results than planning and construction of formal organizations. This timely book contains cases of risk and threat where the former strategy succeeds and the latter fails. The wealth of cases presented includes the Marburg virus outbreak in Angola, bird flu, health insurance after the Tsunami, and the Tjorn bridge catastrophe in Sweden. Graduate and postgraduate students in business and management schools, as well as academics taking teaching courses in risk management across disciplines should not be without this book. Risk management specialists will also find this book invaluable.
1. Introduction: Action Nets Barbara Czarniawska 2. Risk and Organizing - The Growth of a Research Field Ulla Eriksson-Zetterquist 3. Marburg Virus, or a Story of Preparedness Andreas Diedrich 4. Bird Flu - Threat or Opportunity? Kajsa Lindberg 5. Welfare Services - An Area for Risk Management? Lars Noren 6. Adventure Tourism: Making Risk Safe Eva Gustavsson 7. A Net of Actions in the Tracks of Storm Gudrun David Renemark 8. The Tjorn Bridge Catastrophe - On Building a New Bridge Out of an Old One Lars Walter 9. Small Time Breaks Tobias Engberg 10. The Aesthetic Threat Peter Zackariasson 11. Conclusions: Plans or Well-practiced Improvisation? Barbara Czarniawska References
Includes bibliographical references (p. 170-175) and index.
Translated from the Swedish.
oif 22/05/13
Loan
Keywords: Organizational behavior; Industrial organization; Risk management; Crisis management